Effect of Temperature on the Mechanical Properties and Deformation Mechanism of a High Mn Steel With Composite Structure - Chen, Xiaoman; Wang, Yuhui; Xiong, Jianchao; Li, Guoyang; Tian, Yanzhong; Cao, Wenquan; Wang, Tiansheng (Frontiers in Materials, 2020)
A composite high manganese structure comprising recovered and recrystallized structures was prepared using a single-phase austenitic Fe-30Mn-0.14C-7Cr-0.26Ni steel by cold rolling and annealing. The yield strength and elongation of the composite increased simultaneously, when the tensile temperature decreased from room temperature (RT) to low temperature (180 C). The composite structure exhibited a good combination of strength and ductility at RT and 180 C. The notable mechanical properties at low temperature can be attributed to the enhanced strain-hardening capability via introducing multiple deformation mechanisms in the composite structure.